Ultra‐Compliant Indwelling Elastomer Balloons Improve Stability and Performance of Bioengineered Human Mini‐Hearts. Issue 8 (4th March 2022) - Roberts, Erin G.; Mak, Suet Yee; Wong, Andy On-Tik; Tran, David D.; Lee, Eugene K.; Kurokawa, Yosuke K.; Jennbacken, Karin; Wang, Qing‐Dong; Lieu, Deborah K.; Hajjar, Roger J.; Costa, Kevin D.; Li, Ronald A.
Abstract : Animal models used by the pharmaceutical industry to define drug safety and efficacy are expensive, resource‐intensive, subject to interspecies differences, and often fail to predict human responses. Therefore, engineered human tissue preparations are gaining importance as in vitro models to address translation from preclinical data to clinical outcome. Methods that improve fabrication consistency, usability, and physiological relevance of tissues are crucial. For cardiac applications, the goal is to form a miniature 3D chamber that mimics the physiology and biomechanical properties of the ventricle, allowing the measurement of clinically relevant endpoints, such as pressure–volume relationships, which cannot be obtained with simpler constructs. Despite advances in biofabrication, a perfusable mini‐ventricle with a competent endocardium remains an unmet challenge, resulting in thin‐walled organoids that are fluid permeable. A novel method is developed and validated for improving the stability and performance of the herein described human mini‐heart model by creating an ultra‐compliant elastomer balloon for hollow‐organ engineering applications. Balloon properties, tissue formation, and biological data are examined. Findings demonstrate a thin permanent lining, which is retained during testing and permits tissue contraction, functions to eliminate leakage, increase uniformity, and enable multiday longitudinal measurements. Biological data presented herein show reduced variability across measured cardiac parameters when compared to our previously published fabrication method. Abstract : Herein, a novel method is presented for improving the stability and performance of tissue‐engineered human mini‐heart models by creating an ultra‐compliant elastomer balloon for hollow‐organ engineering applications. Findings demonstrate a thin permanent lining on the inside of the chamber, which is retained during testing and permits tissue contraction, functions to eliminate leakage, increase uniformity, and enable multiday longitudinal measurements.